EMPOWERMENT OF THE UMKM COMMUNITY IN UTILIZING PT PLN CSR FUNDS BY BAITULMAAL MUAMALAT REPRESENTATIVE OF WEST JAVA - Walidain, Khoiril; Laila Nurwulan, Riany (Universitas Pasundan, 2025)
This study assesses how Baitulmaal Muamalat West Java Representative empowers MSME actors in the community using PT PLN CSR funds. Through a number of efforts, including social mapping, skills development, licensing assistance, and infrastructure development, this program aims to improve community welfare. The purpose of this study is to show that the program can improve the capabilities and independence of MSME actors. However, there are still some problems that need to be resolved, such as the complexity of choosing an ideal location and fluctuations in raw material prices. From a theoretical perspective, this study advances our understanding of social welfare and economic empowerment, while its practical consequences help professional social workers to create more successful empowerment initiatives. This MSME community empowerment program has the potential to be a successful model in using CSR funds for inclusive and sustainable community development in the future with larger initiatives and ongoing collaboration. The research method used in this study is qualitative research, where this study attempts to describe how community empowerment in MSME actors can run through the use of Corporate Social Responsibility (CSR) funds. The researcher conducted this study with the aim of obtaining complete and in-depth knowledge, information, and descriptions. The data collection technique is carried out through observation, interviews, and documentation studies obtained from the results of MSME actors in the community using PT PLN CSR funds. The results of research that has been conducted on the empowerment of MSME actors in the utilization of PT PLN CSR funds by Baitulmaal Muamalat, West Java representative, that the end of this program shows the success of the planning and implementation of programs aimed at improving the local economy and community welfare.